2021
DOI: 10.3389/fclim.2021.763420
|View full text |Cite
|
Sign up to set email alerts
|

Open Science Expectations for Simulation-Based Research

Abstract: There is strong agreement across the sciences that replicable workflows are needed for computational modeling. Open and replicable workflows not only strengthen public confidence in the sciences, but also result in more efficient community science. However, the massive size and complexity of geoscience simulation outputs, as well as the large cost to produce and preserve these outputs, present problems related to data storage, preservation, duplication, and replication. The simulation workflows themselves pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Many of these impediments could be mitigated by working with a curator who offers recommendations to improve the dataset before its publication. As Mullendore et al note, “Curation tasks should involve partnerships between scientific and data experts to take advantage of their respective knowledge and skills” [ 18 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these impediments could be mitigated by working with a curator who offers recommendations to improve the dataset before its publication. As Mullendore et al note, “Curation tasks should involve partnerships between scientific and data experts to take advantage of their respective knowledge and skills” [ 18 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers wrestle with documentation and metadata in their own work due to lack of access to standards and templates, which is a drain on resources like time and labor [ 4 , 21 ]. Mullendore et al reported that some researchers spend significant amounts of their time curating their data, sometimes “over 50% of their funded time” [ 18 ]. When Johnston et al asked researchers what curators could do to help them in their work, overwhelmingly they responded with anything they could hand off to a curator so the researcher didn’t have to deal with it [ 3 ].…”
Section: Literature Reviewmentioning
confidence: 99%